THE ROLE OF INNOVATION IN ENHANCING FINANCIAL PERFORMANCE IN YOGYAKARTA'S CREATIVE INDUSTRY - Andreas Mahendro Kuncoro; Melvin Rahma Sayuga Subroto; Eric Ohara (Transpublika Publisher, 2024)
This study explores the impact of various types of innovation—organizational, process, product, and business model innovations—on the financial performance of firms in Yogyakarta's creative industry. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 57 creative industry firms. The findings indicate that organizational innovation significantly enhances process and business model innovations, which in turn positively affect financial performance. However, the direct impact of organizational innovation on product innovation is not significant, suggesting the need for a more integrated approach to foster product development. The study highlights the essential of innovative practices and adaptive business models in driving financial success in the creative industry. These insights are crucial for managers and policymakers aiming to boost the financial performance of creative firms through strategic innovation.